Solar Radiation as Energy Source for Plants Water Pumping System - Othman, Raudhah; Zainal Alam, Muhd Nazrul Hisham (Research Progress in Mechanical and Manufacturing Engineering, 2023)
A solar based water pumping system for watering of plants in garden was established in this study. Daily energy generation for the period of 3 months were assessed and the effectiveness of the solar radiation for powering up the pump was evaluated. A complete solar photovoltaic (PV) system which includes 50W solar panel, solar charge controller, AC-DC converter and 12V DC battery was established in the work where it was used to water Aloe Vera plants. Data shows that water flow rate reached its maximum value during sunny days were radiation at its peak and recorded a very low rates during rainy days. An almost 45-50% reduction in the water flow was seen during the bad weather with least solar radiation. Despite the bad weather, water supply was not halted and sufficient energy have been generated to ensure a consistent pump operation for the growth of the Aloe Vera plants. In can be concluded that, solar based pump is indeed suitable for watering plants in the garden even though at times solar radiation is not at its peak. This is because it seems that plants did not need to be watered on 24 hours basis. On contrary, minimum volume of water is needed to ensure good plant growth.